Demand forecasting for successive generations of mobile telecommunication service in Ethiopia - Birku Reta Entele; Bikram Acharya (Cogent Economics & Finance, 2021)
The Ethiopian telecommunication market has been expanding slowly due to supply side constraints. However, these days, government has already announced to open market to the private operators and in this environment, the upcoming mobile telecommunication market, where 4 G service was already introduced in 2015, is becoming more substitutive and competitive. Thus, this study aim to forecast the switchers and leapfrogers demand for 3 G and 4 G mobile data services in Ethiopia. In order to do so, firstly, we investigated consumer preferences for mobile data generation services. Secondly, we estimated the mobile phone diffusion using Bass model to predict the future potential market size. Finally, we combined both models and forecasted the switchers and leapfrogers demand for 3 G and 4 G mobile data services. The result reveals that, by 2025, the 3 G and 4 G data service subscribers are forecasted to be 40 and 1.93 million, respectively, including both switchers and leapfrogers adoption. The policy implications are: (1) Service provider should adjust its service supply plan as per the forecasted demand. (2) Service provider should charge its service package strategically considering demand elasticity and finally, the service provider should make proper expansion of 4 G infrastructure since consumers are verging towards 4 G data services.
Keywords: 330; Demand forecasting; Ethiopia; leapfrogers; mobile data services; switchers